Patient Education and Quality of Life in Type 2 Diabetes: Insights from a Narrative Review - Stróżna, Małgorzata; Stróżna, Katarzyna; Chmura, Katarzyna; Zimnoch, Barbara; Rendaszka, Katarzyna; Kowalska, Katarzyna; Pyziołek , Marta; Bonarska, Marta; Kwaśniewska, Paulina; Najbar, Joanna Monika (Quality in Sport, 2025)
Type 2 diabetes mellitus (T2DM) significantly impairs the physical, psychological and social dimensions of life in affected individuals (1). Proper disease control requires effective self-management to reduce the risk of complications and optimize long-term functioning (2). These activities should extend beyond glycemic regulation to include rehabilitation and complication prevention. Patient education is therefore considered a crucial factor enabling individuals to engage in effective self-management (3). Objective: This review aims to summarize evidence on how patient education influences quality of life (QoL) in people with T2DM (4). Methods: A narrative review was conducted by searching PubMed, Scopus, and Google Scholar for literature from 2010 to 2025 (5). Results: Existing research consistently indicates that structured educational interventions — including Diabetes Self-Management Education (DSME), lifestyle coaching and digital tools — contribute to improved glycemic control, greater disease awareness and enhanced mental health outcomes (6, 7). Educational programs support emotional well-being, increase self-efficacy and strengthen social participation among people with T2DM (8, 9). Conclusions: Patient education is essential for improving QoL and clinical outcomes in Type 2 diabetes (T2DM) patients (10). Personalized and culturally adapted education should be integrated into standard care (11).